Analysis on Grammatical and Lexical Cohesion Found in BBC News Instagram Post Captions - Diniati Andre Come Rihi; Putu Chrisma Dewi; I Gusti Nyoman Putra Kamayana (LPPM Universitas Dhyana Pura, 2023)
This study aimed to identify the types of grammatical and lexical cohesion in the BBC news Instagram post caption. The descriptive qualitative method was used in this study. The data sources were taken from BBC news Instagram post caption start from July 1st 2022 until June 30th 2023. The data was analysed using theory of Halliday and Hasan (1976) about grammatical and lexical cohesion. Based on the results of the analysis, the types of grammatical cohesion were found in Instagram captions were: reference with used 14 data, substitution 1 data, ellipsis 3 data, and conjunction 5 data. The results showed that the most dominant type of grammatical cohesion is reference. The types of lexical cohesion were found reiteration with used 13 data and collocation 4 data. The most dominant type of lexical cohesion is repetition. The total data of analysis grammatical and lexical cohesion in the BBC news Instagram caption are 40 data and all types were found in this analysis.